2016
DOI: 10.1002/jemt.22692
|View full text |Cite
|
Sign up to set email alerts
|

Increase of forage dryness induces differentiated anatomical response in the sheep rumen compartments

Abstract: The aim of this study was to investigate how the Surface Enlargement Factor (SEF) and the epithelial keratinization degree of sheep rumen change in response to phytomass production, and to forage fiber and water content during the pasture vegetative cycle. The study used eighteen sheep nourished with dry hay and cereals during the winter season and with fresh hay during the pasture vegetative cycle. We collected samples from rumen indicative regions for two consecutive years characterized by different rainfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This type of diet, in experimentations regarding sheep grazing, demonstrated how, feeding on this forage type, increased the rumen keratinization [12] and lowered the absorption of nutrients. For this reason, it is not feasible to use sheep grazing as a method for grassland recovery [20,21] and mowing should be the best practice in the restoration of Brachypodium-invaded grasslands [12]. Mowing is considered one of the most appropriate management types for ensuring the high conservation value of grasslands [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This type of diet, in experimentations regarding sheep grazing, demonstrated how, feeding on this forage type, increased the rumen keratinization [12] and lowered the absorption of nutrients. For this reason, it is not feasible to use sheep grazing as a method for grassland recovery [20,21] and mowing should be the best practice in the restoration of Brachypodium-invaded grasslands [12]. Mowing is considered one of the most appropriate management types for ensuring the high conservation value of grasslands [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The natural and semi-natural pastures in the central Apennines in Italy are used as trophic resources for zootechny, but the increase in summer aridity causes a decrease in the pastoral value of the grasslands; in fact, it is registering an anticipation of the moment of pasture maximum flowering and a shortening of the period between maximum flowering and maximum dryness of pastures. This fact reflects on a lower availability of both forage quality and quantity; the increase in drought stress is therefore detrimental to the sustainability of extensive sheep farms because it affects the morpho-functional features of the animals [1,2,3,4] and greatly reduces milk production [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that papillary morphometry can vary with the type of diet [24][25][26] especially in growing animals. It is therefore imperative that studies specify the type of feed used and that such feeding regimens be maintained in experimental groups.…”
Section: Discussionmentioning
confidence: 99%